Peran Niat Pembelian Hijau Dalam Memediasi Hubungan Antara Pengetahuan Produk Hijau, Kepercayaan Hijau Terhadap Keputusan Pembelian Produk Skincare Avoskin - Dessiliya; Adi Mursalin; Muchammad Ariffin (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2025)
Green products, which are environmentally friendly and sustainable, have become a choice for consumers who care about the environmental impact of their consumption. However, the decision to purchase green products is influenced not only by consumers' knowledge of the products but also by their level of trust in the green claims made. This study aims to examine how green purchase intention mediates the relationship between knowledge of green products and green trust on a person's purchase decision. The research method uses a quantitative exploratory approach with the distribution of questionnaires to 147 respondents and is analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 3.0. The results indicate that knowledge of green products and green trust have a positive and significant effect on purchase decisions, both directly and indirectly through purchase intention. Mediation testing using the bootstrapping approach shows that purchase intention is able to partially mediate the relationship between knowledge, trust in purchase decisions. These findings indicate that increasing consumer knowledge and trust in green products needs to be accompanied by efforts to build strong purchase intentions in order to encourage sustainable purchasing decisions.